Behind the Scenes of Subtitling - Ágostai, Katalin (Orpheus Noster, 2026)
When translating films and series, I have often experienced how complex and difficult my work is, especially when translating from Japanese. Translating an original English film is like performing an incredible balancing act, e.g., tightrope walking. Translating a Japanese text is, by contrast, like tightrope walking with an umbrella in one hand (with a ball rolling on the umbrella), and the original Kojiki text in the other hand as one tries to verbally adapt it to the modern Japanese language. In my article, I would like to offer a glimpse into the background of this almost absurd performance through my work, and briefly show what an audiovisual translator, more commonly known as a dubbing scriptwriter, can do with sign language, lyrics, dialects, and other Japanese-specific themes in films and series as he or she adapts all these to the world of subtitles.